2010
DOI: 10.1063/1.3305637
|View full text |Cite
|
Sign up to set email alerts
|

Local conductivity and electric field analysis of Ag-based conductive adhesive by transmission electron microscopy

Abstract: The conduction mechanism in Ag-based conductive adhesive, which has attracted the attention of researchers, has been intensively studied by the in situ observations of transmission electron microscopy (TEM) and by using special methods that employ the use of microprobes; Ag-based conductive adhesive is considered as an alternative to Pb-free solders. A current versus voltage (I-V) curve measured by using a microscope exhibited peculiar fluctuations, which implied an irreversible change in the internal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, it has been reported that the I -V relationship for a cured Ag-based conductive adhesive is changed from nonlinear to linear character after supplying a current. From in situ TEM observations, deformations of fillers have actually been observed during biasing [29]. Both electromigration and local temperature increase due to Joule heating have been suggested to account for such deformations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the I -V relationship for a cured Ag-based conductive adhesive is changed from nonlinear to linear character after supplying a current. From in situ TEM observations, deformations of fillers have actually been observed during biasing [29]. Both electromigration and local temperature increase due to Joule heating have been suggested to account for such deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The TEM observations in our recent study revealed the occurrence of morphological changes in the Ag fillers used in Ag-based conductive adhesives; such changes appear to influence the resistivity of these adhesives. 8) In the present paper, we give a brief report of another application of in situ Fig. 4 (a), (b), (c) Bright-field images of cross-sectional specimens containing 88 mass%, 92 mass%, and 94 mass% of Ag fillers.…”
Section: Correlation Between Microstructure and Anomaly In Resistivitmentioning
confidence: 99%
“…Some of the present authors have carried out simultaneous observations of the microstructure and the current-voltage (I-V) characteristics 8) of thin-foil specimens of Ag-based conductive adhesive. They conducted an in situ experiment by using a special equipment called double-probe piezodriving holder, 9,10) which is ideal for carrying out conductivity measurements in a nanometer-scale area.…”
Section: Introductionmentioning
confidence: 99%